Contextual Teaching and Learning Using Local Content Material on Students’ Reading Comprehension at a Junior High School in Indonesia - Pratama, Aryawira; Sumardi, Mayang Sastra (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
One of the important skills in learning English is reading. There should be an effective strategy to teach this skill. This research is combining the form of contextual teaching and learning with local content material. By combining these two terms, there must be an increasing result from the students mastering reading skills. This research aims to examine the impact of contextual teaching and learning using the local content material on students’ reading comprehension at a junior high school in Indonesia. The population of its research is eighth-grade students, and two classes were selected as samples experimental class (treatment) and controlled class. This experimental study used reading tests as instruments to get the data. The test was formatted into multiple-choice items, consisting of pre-test and post-test. The researchers used the pre-test, treatment, and post-test techniques to collect the data. But in the control class, no treatment was applied to mastering reading skills. There was a significant effect in the treatment class than in the control class. It was proven by the effect size’s score of medium effect showed .5 deviation. It indicated that the treatment of using contextual teaching and learning with local content was successful.